HEALTH EDUCATION TO INCREASE ADOLESCENTS' KNOWLEDGE ABOUT PREVENTING PREGNANCY - Arini, Diyah; Fatimawati, Iis; Hastuti, Puji; Ernawati, Dwi; Budiarti, Astrida; Saidah, Qori’ Ila; Faridah (Community Service Journal of Indonesia, 2023)
Adolescence is a period of rapid growth and development both physically, psychologically and intellectually. The typical nature of teenagers is that they have a great sense of curiosity, like adventure and challenges and tend to be brave enough to take risks in their actions without prior careful consideration. If the decisions taken in dealing with conflict are inappropriate, they will fall into risky behaviour and may have to suffer short-term and long-term consequences in various physical and psychosocial health problems. The nature and risky behaviour of adolescents requires the availability of caring adolescent health services that can meet the health needs of adolescents, including services for reproductive health. The aim of this community service activity is to increase teenagers' knowledge about preventing teenage pregnancy so that it can reduce the incidence of teenage pregnancy. This health education was carried out via online zoom meeting. This activity is education about preventing pregnancy in teenagers targeting high school and vocational school students in the Surabaya, Sidoarjo and Gresik regions Education attended by 122 teenagers. Before the counselling was carried out, questionnaires were distributed online via Google form. Results were obtained from 122 participants consisting of 54 (44%) high school students, while 68 (56%) were students, of which 13 (10%) % had not received Sex education. And after conducting health education, it was found that 105 (86%) of respondents' knowledge data was good. The influence of the environment, social media, cultural acculturation, and adolescent knowledge is one of the causes of promiscuous sexual behavior. The active role of parents, teachers and the community is needed to invite and provide motivation as well as health education to increase teenagers' knowledge in preventing the occurrence of promiscuous sex so that teenagers can behave more appropriately.